2018
DOI: 10.1093/ilar/ily018
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and In Vivo Characterization of Vaccine Adjuvants

Abstract: Many different adjuvants are currently being developed for subunit vaccines against a number of pathogens and diseases. Rational design is increasingly used to develop novel vaccine adjuvants, which requires extensive knowledge of, for example, the desired immune responses, target antigen-presenting cell subsets, their localization, and expression of relevant pattern-recognition receptors. The adjuvant mechanism of action and efficacy are usually evaluated in animal models, where mice are by far the most used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 140 publications
(168 reference statements)
0
4
0
Order By: Relevance
“…This is important, especially for protein-based vaccines [43]. Adjuvants in vaccine production facilitate the induction of adequate immune response in place of an antigen [216,217]. Recently, Cibulski et al [218] reported QB-90, a Quillaja brasiliensis leaf saponin fraction, stimulating a systemic immune response and promoting a local and transient immune response in mice model when administered up to 24 h before the administration of antigen.…”
Section: Global Issues Future Perspectives and Recommendationsmentioning
confidence: 99%
“…This is important, especially for protein-based vaccines [43]. Adjuvants in vaccine production facilitate the induction of adequate immune response in place of an antigen [216,217]. Recently, Cibulski et al [218] reported QB-90, a Quillaja brasiliensis leaf saponin fraction, stimulating a systemic immune response and promoting a local and transient immune response in mice model when administered up to 24 h before the administration of antigen.…”
Section: Global Issues Future Perspectives and Recommendationsmentioning
confidence: 99%
“…Finally, a higher antigen dose can lead to greater production of the follicular helper T cells that govern the germinal center responses [ 27 ]. These are, however, speculations that need to be proven using in vivo tracking studies: for example, using radio- or fluorescently labeled proteins as described in [ 28 ]. It should be noted that it cannot be used as a general rule that depot formation at the site of injection is a prerequisite for a strong T cell response, clearly illustrated by GLA-SE [ 29 ] and AS01 [ 30 ], these being two non-depot-forming adjuvants both documented to induce durable Th1 responses.…”
Section: Vaccine Pharmacokinetics and Immune Responsesmentioning
confidence: 99%
“…This type of vaccines overcomes some of the safety concerns associated with live attenuated or inactive vaccines [ 10 ]. Furthermore, as they are designed using specific antigens, they can be targeting different aspects of the infection, optimized as the research progresses and provide additional immune responses for more complex pathogens, such as Mtb [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While being very safe, subunit vaccines cannot rely solely on the antigen to achieve a desired effect as they are generally poorly immunogenic [ 10 ]. Adjuvants are needed in their formulation in order to increase immunogenicity, decrease the antigen dose, ensure a targeted delivery and optimize the antigens interaction with the immune cells [ 10 , 11 ]. Undeniably, adjuvants are an important part of new subunit vaccines design and in general, adjuvants identification, design and characterization is essential to modern vaccines formulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%